Pengaruh Kombinasi Sistem Tanam Non Konvensional dan Cekaman pH Basa Larutan Nutrisi Terhadap Daya Hasil Kubis Bunga (Brassica oleracea L. Var. botrytis) - Rynaldi Esa Prayogo; Rommy Andhika Laksono; Yayu Sri Rahayu (JURNAL PERTANIAN, 2025)
Cauliflower production in Indonesia decreased by 38.79% from 2021 to 2022, partly due to Shrinking agricultural land. Non-conventional cultivation methods, such as wick hydroponics and aeroponics, offer alternative solutions to traditional farming. In addition, one key factor affecting cauliflower yield is abiotic stress, particularly high pH levels in nutrient solutions. This study aims to examine the effect of combining non-conventional growing systems with alkaline pH stress on the growth and yield of cauliflower (Brassica oleracea L. var. botrytis) cultivar Larissa F1 This research used an experimental approach with a single factor Completely Randomized Design (CRD) with six treatments, each replicated four times, resulting in 24 experimental units and a total of 72 plants. The treatments included wick hydroponics and aeroponics under three pH ranges: 6–7, 7–8, and 8–9. Data were analyzed using ANOVA and further tested with Duncan's Multiple Range Test (DMRT) at a 5% significance level. Results showed that wick hydroponics with pH 8–9 produced the highest average leaf count at 14 days after planting (7.5 leaves). Aeroponics with pH 6–7 yielded the highest average leaf count at 42 days after planting (13.8 leaves), and also achieved the greatest average curd height and root length (10 cm and 62.5 cm, respectively), although these were not significantly different from other treatments.